2018 52nd Asilomar Conference on Signals, Systems, and Computers 2018
DOI: 10.1109/acssc.2018.8645260
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Big Data Over Networks Via The Logistic Network Lasso

Abstract: We apply network Lasso to solve binary classification and clustering problems on network structured data. In particular we generalize ordinary logistic regression to non-Euclidean data defined over a complex network structure. The resulting logistic network Lasso classifier amounts to solving a convex optimization problem. A scalable classification algorithm is obtained by applying the alternating direction methods of multipliers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…This paper substantially extends our prior work on networked linear models for regression and classification [1], [28], [29], [47]. We have recently derived conditions on the data network structure such that nLasso accurately learns a clustered graph signal [29].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…This paper substantially extends our prior work on networked linear models for regression and classification [1], [28], [29], [47]. We have recently derived conditions on the data network structure such that nLasso accurately learns a clustered graph signal [29].…”
Section: Introductionmentioning
confidence: 66%
“…Algorithm 1 can be implemented as message passing over the empirical graph G (see [1]). During each iteration, messages are passed over each edge {i, j} ∈ E in the empirical graph.…”
Section: B Computational Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that Algorithm 1 can be implemented as message passing over the empirical graph G (see [1]). During each iteration, messages are passed over each edge {i, j} ∈ E in the empirical graph.…”
Section: Computational Complexitymentioning
confidence: 99%
“…2, we depict the normalized mean squared error (NMSE) ε := w − w 2 2 / w 2 2 incurred by Algorithm 1 (averaged over 10 i.i.d. simulation runs) for varying connectivity, as measured by the empirical averageρ of ρ (1) and ρ (2) (having same distribution). According to Fig.…”
Section: Two-cluster Datasetmentioning
confidence: 99%